Differential associations of modifiable and non‐modifiable dementia risk factors with memory decline and hippocampal volume loss in Aβ‐ and Aβ+ cognitively normal older adults. (31st December 2021) - Rosenich, Emily; Pase, Matthew P; Yassi, Nawaf; Fripp, Jurgen; Laws, Simon M; Fowler, Christopher J; Rowe, Christopher C; Masters, Colin L; Maruff, Paul T; Lim, Yen Ying; Group, AIBL Research
Abstract: Background: The extent to which modifiable and non‐modifiable risk factors contribute to cognitive decline in older people remains unclear. We sought to determine the association of modifiable and non‐modifiable components included in the Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE) score with memory decline and brain volume loss in cognitively normal (CN) older adults, taking Aβ status into account. Method: AIBL study participants (age range: 60‐90) who completed ≥2 neuropsychological assessments and an Aβ PET scan (N=626) were included in this study. We computed the standard CAIDE (age, sex, APOE ε4 status, education, hypertension, body mass index, hypercholesterinemia, physical inactivity), and a modifiable CAIDE (modCAIDE; education, modifiable vascular risk factors) for each participant. Aβ+ was classified using a Centiloid ≥25. Linear mixed models assessed interactions between each CAIDE score on episodic memory (EM) and hippocampal volume (HV) over time in Aβ‐ and Aβ+ CNs. Non‐modifiable variables from the standard CAIDE (age, sex, ε4) were included as separate predictors in all modCAIDE models to assess differential associations. Result: We observed a significant standard CAIDE x time interaction on EM decline in Aβ+ (β=‐0.08(0.04); p=0.02) and Aβ‐ participants (β=‐4.07(1.13); p<0.001), and a significant standard CAIDE x time interaction on HV loss in Aβ+ participants only (β=‐0.06(0.02); p=0.003). When modifiable and non‐modifiable CAIDE components were considered separately, we observed a significant ε4 x time interaction only for EM decline (β=‐0.32(0.07); p<0.001) and HV loss (β=‐0.13(0.04); p<0.001) in Aβ+ participants, but no significant modCAIDE x time interaction (both p's>0.29). In Aβ‐ participants, we observed a significant modCAIDE x time interaction on memory decline (β=‐0.04(0.02); p=0.02), but no significant ε4 x time interaction (β=‐0.07(0.04); p=0.11). No significant ε4 x time or modCAIDE x time interactions were observed for HV loss in Aβ‐ participants. Conclusion: Our results are consistent with previous studies showing that ε4 is associated with an increased rate of EM decline and HV loss in Aβ+ CNs. In Aβ‐ CNs, lower prevalence of modifiable cardiovascular risk factors was associated with better EM performance over time, suggesting interventions to reduce modifiable risk factors could be beneficial in this group.